Improving management of fever in neutropenic children with cancer across multiple sites. (28th January 2021) - Anderson, Katrina; Bradford, Natalie; Edwards, Rachel; Nicholson, Jessica; Lockwood, Liane; Clark, Julia E.
Abstract: Objective: To evaluate the effectiveness of a clinical pathway in achieving antibiotic administration in less than 60 minutes for children with cancer, presenting with fever and neutropenia. Secondary objectives were to determine association between time to antibiotics (TTA) and other variables including fever duration, location of care and intravenous access types. Methods: Following introduction of the clinical pathway, we collected prospective data about management of all cases that did and did not use the pathway across multiple sites over 16 months. A follow‐up audit was conducted after 12 months. Results: We evaluated a total of 453 presentations. Use of the clinical pathway was significantly associated with achieving TTA in less than 60 minutes (RR 0.69, 95% CI 0.56–0.85, p = <0.001). Despite varying use of the pathway over time, the median time to antibiotics was achieved in both the initial study period (57 minutes) and sustained at follow‐up (60 minutes). TTA was also associated with types of intravenous access device and location of care and with length of stay. We did not find any association between TTA and any other variables. Conclusion: Clinical pathways improve fever management in this patient cohort. Ongoing education and auditing to identify factors which impact processes of care are necessary.